Pacific Waters Pathways and Vertical Mixing in the CESM1‐LE: Implication for Mixed Layer Depth Evolution and Sea Ice Mass Balance in the Canada Basin. Issue 2 (12th February 2022) - Lavoie, Juliette; Tremblay, Bruno; Rosenblum, Erica
Abstract: We compare the vertical hydrography of the Community Earth System Model Large Ensemble (CESM1‐LE) with observations from two specific periods: the Arctic Ice Dynamics Joint Experiment (AIDJEX; 1975–1976) and Ice‐Tethered Profilers (ITP; 2004–2018). A comparison between simulated and observed salinity and potential temperature profiles highlights two key model biases in all ensemble members: (a) an absence of Pacific Waters in the water column and (b) a slight deepening of the May mixed layer contrary to observations, which show a large reduction in the mixed‐layer depth and an increase in stratification over the same time period. We examine processes controlling the sea ice mass balance using a one‐dimensional vertical heat budget in the light of the model limitations implied by these two biases. Results indicate that remnant solar heat trapped beneath the halocline is mostly ventilated to the surface by mixing before the following melt season. Furthermore, we find that vertical advection associated with Ekman pumping has only a small effect on the vertical heat transport, even in early fall when the winds are strong and the pack ice is weak. Lastly, we estimate the impact of the missing Pacific Waters at 0.40 m of reduced winter ice growth. Plain Language Summary: The year 2007 marked the beginning of a new Arctic paradigm, with a large decrease in sea ice extent at the end of the melt season in the Pacific sector of the Arctic. The proximity of this sea ice loss to the Bering Strait raises the question as to whether ocean heat of Pacific origin beneath the mixed layer is transported upward (ventilated) to the surface despite the strong stratification. In this article, we look at the ventilation, or absence thereof, of Pacific Waters in the Community Earth System Model Version 1 Large Ensemble. We find that Pacific Waters are completely absent in the Canada Basin of the Arctic in the CESM1, and that the simulated winter mixed layer is thickening in the transition to a seasonally ice‐free Arctic, in contrast with observations from the 1970s and the 2010s. A simple 1‐dimensional vertical heat budget of the water column suggests that ventilation of Pacific Waters could play an important role in the sea ice mass balance on time scales of a few years. Key Points: There is an absence of Pacific Waters in the Canada Basin in the Community Earth System Model Version 1 Large Ensemble (CESM1‐LE) The CESM1‐LE does not simulate the large shoaling of the mixed‐layer observed between 1975–1976 and 2004–2018 The impact of missing Pacific Waters is estimated at 0.40 m of reduced winter ice growth using a 1D heat budget